ANALYSIS OF MAIN DEMOGRAPHIC AND PROFESSIONAL INDICATORS RELATED TO THE ACTIVITIES OF MEDICAL ASSISTANTS WORKING IN THE CENTERS FOR EMERGENCY MEDICAL ASSISTANCE IN THE REPUBLIC OF BULGARIA - Deyana Todorova; Albena Andonova (Peytchinski Publishing, 2023)
PURPOSE: The presented article aims to determine the main demographic and professional indicators related to the activities of medical assistants working in emergency medical care in the Republic of Bulgaria. MATERIAL AND METHODS: In this regard, scientific developments, reports and publications of researchers and experts in this field were studied and analyzed. A survey was conducted through an interview and a direct anonymous survey in the first quarter of 2019 with 325 respondents. RESULTS: The problems and the current state of the work of the medical assistants working in emergency medical care are the subject of lively discussions on a global and national scale. This emphasized interest and attention stems from the global issues that are the subject of their work. CONCLUSIONS: Urgent measures are needed to attract young medical assistants to work in emergency medical centers, to provide a sufficient number of medical specialists in the teams, to increase salaries, to provide modern medical equipment, to introduce telemedicine, etc.